A "Queer-Looking Compound": Race, Abjection, and the Politics of Hawaiian Poi. Issue 2 (3rd July 2017) - Hobart, Hiʻilei Julia
Abstract: The ecological, cosmological, and genealogic meanings of kalo (taro) and the foods made from it bind the practice of eating poi, an important traditional staple food, to both material and cultural concepts of Hawaiian identity. During the nineteenth century, the taste of foods like poi became a subject of debate among newcomers to the archipelago, who used the language of disgust, queerness, and civility to distinguish Euro-American whiteness from indigeneity through foodways. While discourses about the palatability of poi were, and still are, typically couched in the language of personal preference, an examination of historical sources reveal settler abjection to instead be a culturally conditioned approach to Native taste and foodways. This article uses the subject of kalo to extend histories of colonial tastemaking into the ongoing dimensions of settler terrain through discourse analysis of nineteenth century travelogues, popular media, and Native epistemology in order to reveal the interlocking logics of taste and territory.